Nyanyian PanjangBujang Si Undang as oral tradition in Melayu Ethnic; an alternative approach for mental revolution - Erni Erni; Hasanuddin WS; Harris Effendi Thahar; Yasnur Asri (International Conferences on Educational, Social Sciences and Technology)
This study aimeds to describe the form of mental revolution in NyanyianPanjangBujang Si Undang which is viewed from six aspects tunjuk ajar, namely faith to God, honesty, intelligence, integrity, caring, and nationality. This study was a qualitative research using descriptive method. The data in this study were the character of educational value from the narrator, characters’ utterance and characters’ act which werecollected through format of data inventory. The data were analyzed based on Miles dan Hubeman’s models through three steps; data reduction, data display and conclusion. There are six forms mental revolution on the characters of educational value in NyanyianPanjangBujang Si Undangnamely faith to God, honesty, intelligence, integrity, caring, and nationality. Therefore, NyanyianPanjangBujang Si Undang as oral tradition inheritance can be used as the alternative in supporting the education from local wisdom of Melayu society to solve the problems of morality and ethic.